Improving yam yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Scientists at the University of Nigeria have shown that treating tubers of white yam ( Dioscorea rotundata) with the growth regulator IBA before planting ensures dormancy is broken and results in more uniform crop establishment and higher yields....